Alternative Approaches in Development: Perspectives on Religion- and Community-Based Participatory Development - Destia Henni; Widia Sukma; Nurhijjah N; Akdila Bulanov (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The concept of development has generally focused on economic growth and modernization, often neglecting the social, cultural, and religious aspects of society. As a result, various problems such as social inequality, poverty, and low community participation continue to occur. These conditions have given rise to alternative development approaches that emphasize human welfare, social justice, community empowerment, and active public participation in the development process. One form of this alternative approach is religion-based development, which uses religious values as guidelines in building social life within society. This study aims to explain alternative development and analyze the role of religion in supporting social development. The method used in this study is a literature review by examining various books, journals, and scientific sources related to the sociology of development. The results of the study show that religion-based development contributes to strengthening social solidarity, increasing public awareness, and encouraging economic and social empowerment through various religious activities. Therefore, religion-based alternative development approaches can become one of the solutions for development that is more participatory, humane, and oriented toward social welfare.